2002
DOI: 10.1055/s-2002-19323
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Catalytic Ketone Allylation with Sn(CH2CH=CH2)4/RSn(CH2CH=CH2)3 Mixtures (R = Et, Bu)

Abstract: In the presence of the monothiobinaphthol (MTB) ligand aryl ketones are allylated by mixtures of Sn(CH 2 CH=CH 2 ) 4 / RSn(CH 2 CH=CH 2 ) 3 (R = Et, Bu) in high e.e. The presence of water suppresses racemic background allylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Under optimized condition with a 3/1/2 ratio of 101/ketone/(R)-BINOL and 2 equiv of MeOH, the allylation product 102 is obtained in high yield albeit modest enantioselectivity. Important improvements in enantioselectivity and chiral modifier loading are seen with the use of 1,1′-binaphthalen-2′-mercapto-2-ol 103 149 (Scheme 56). With 20 mol % of 103 and 40 mol % of water, a number of aryl ketones are allylated with a mixture of 101 and (triallyl)butylstannane (optimized ratio 7/3), to provide the adducts in high yields and enantioselectivities.…”
Section: Scheme 52mentioning
confidence: 99%
“…Under optimized condition with a 3/1/2 ratio of 101/ketone/(R)-BINOL and 2 equiv of MeOH, the allylation product 102 is obtained in high yield albeit modest enantioselectivity. Important improvements in enantioselectivity and chiral modifier loading are seen with the use of 1,1′-binaphthalen-2′-mercapto-2-ol 103 149 (Scheme 56). With 20 mol % of 103 and 40 mol % of water, a number of aryl ketones are allylated with a mixture of 101 and (triallyl)butylstannane (optimized ratio 7/3), to provide the adducts in high yields and enantioselectivities.…”
Section: Scheme 52mentioning
confidence: 99%
“…In fact, the allylation of different phenones using this chiral monothiol could be performed at room temperature and using substoichiometric amounts of the ligand without any further additive, the ee being up to 92% [113]. A mechanistic study showed the great impact of impurities on the enantioselectivity and as result of this study a tetrametallic species was postulated as the catalytic system.…”
Section: Allylation Processesmentioning
confidence: 84%
“…up to 86%. 1 the COST-D24 Programme. We thank a referee for pointing out the possibility of catalysis by (MTB)Sn(allyl)R species.…”
Section: 2mentioning
confidence: 99%
“…In 2002 we identified an unusual asymmetric reaction where, in the presence of catalytic amounts of the chiral ligand MTBH 2 samples of tetraallyltin of 98% chemical purity ketones were allylated up to nine times more selectively than with completely pure Sn(CH 2 CH@CH 2 ) 4 (>99% purity gives <35% ee for PhC(O)Me) (Scheme 1) [1]. Subsequent careful work revealed the selective catalyst is formed from trace amounts of EtSnCl(CH 2 CH@CH 2 ) 2 (3) derived from incomplete reaction of the SnCl 4 and the presence of EtBr (used for Grignard preparation) [2].…”
Section: Introductionmentioning
confidence: 99%